Involuntary Nighttime Urination. (Herbal Treatment) (Texas Journal of Medical Science, 2022)
The article discusses the use of medicinal raw materials and their use in medicine. Phyto preparations are currently prescribed very often. Preparations obtained from medicinal raw materials belong to the category of biologically active additives.